Nanotechnology-based Implantable Drug Delivery: Characterization of Electrospun Temozolomide-Cellulose Acetate Nanofibers - Asyikin Sasha Mohd Hanif; Renatha Jiffrin; Siti Ernieyanti Hashim; Saravana Kumar Jaganathan; Mohamad Ikhwan Jamaludin (International Journal of Nanoelectronics and Materials (IJNeaM), 2026)
Electrospinning is a promising nanotechnology-based method for fabricating drug-loaded nanofibers. In implantable drug delivery systems (IDDS), electrospun nanofibers can offer targeted and sustained drug release owing to their high surface area-to-volume ratio, tunable porosity, and ability to incorporate various therapeutic agents. This study describes the preparation of electrospun cellulose acetate (CA) nanofibers as sophisticated biomaterials loaded with temozolomide (TMZ), a widely used anticancer drug for treating brain tumors. CA nanofibers loaded with TMZ were synthesized by electrospinning CA at a constant concentration of 17% (w/v) and different TMZ loadings (5 mg, 10 mg, and 15 mg). Electrospun TMZ–CA nanofiber membranes were characterized by scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and ultraviolet-visible spectrophotometer (UV-Vis). SEM analysis confirmed uniform, bead-free fibers with increasing diameter as TMZ concentration increased. FTIR and UV-Vis spectroscopy analysis confirmed that TMZ retained its stability and molecular integrity within the CA matrix following fabrication. In addition, sessile drop contact angle studies indicated hydrophobicity, consistent with continued drug release. As TMZ loading increased, the tensile modulus, tensile strength, and elongation at break decreased, reflecting drug disruption in the polymer matrix. In vitro drug release studies revealed a biphasic profile, with 22-26% of the drug released within 8 hours, indicating sustained delivery potential. The cytotoxicity study showed that higher TMZ loading increased and sustained tumor cell killing. This work highlights the effectiveness of electrospinning as a fabrication technique to produce structurally stable, drug-loaded nanofibers, emphasizing their potential as implantable systems for localized chemotherapy.